Divergence Studies in Plus Trees of Neem (Azadirachta indica) - Kaushik, N.; Nautiyal, S.; Kaushik, J.C.; Beniwal, R.S. (Indian Journal of Agroforestry, 2020)
The performance of ninty plus trees of Azadirachta indica collected from different agroclimatic zones of Haryana was studied at HAU Regional Research Station, Bawal for genetic divergence studies. Data on seed morphology, nursery characters, oil content and fatty acid composition of oils was recorded. Six clusters were obtained based on 0' statistic. Maximum plus trees (19) were under cluster 1. Maximum intra-cluster distance (125.928) shown by cluster III is an indicator of selection of parents for hybridization within the cluster. The maximum inter cluster distance (244.342) between cluster III and IV followed by cluster I and III (232.247) indicating wider genetic diversity between the trees in these groups and selection of parents from such cluster for hybridization programmes would help to achieve novel hybrids. These studies revealed that the geographical diversity is not the only factor in determining divergence, therefore, selection of genotypes should be based on genetic diversity. The hybridization between the more diverse genotypes of neem can produce genotypes with high heterotic vigor.